2016
DOI: 10.1007/s00167-016-4269-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soft tissue balancing and distal femoral resection on flexion contracture in navigated total knee arthroplasty

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 36 publications
(48 reference statements)
1
37
0
Order By: Relevance
“…Ligament balancing is essential during TKA and especially difficult to assess and to manage. Experienced surgeons traditionally obtain soft tissue balance using their own subjective "feeling" rather than a scientific perspective [25][26][27][28]. The ligament balancing "feeling" is affected by many factors such as patient obesity, gender, generalized laxity, degree of joint contracture, surgical experience, and even the surgeon's daily condition [29,30].…”
Section: Sensors In Tka 41 General Conceptsmentioning
confidence: 99%
“…Ligament balancing is essential during TKA and especially difficult to assess and to manage. Experienced surgeons traditionally obtain soft tissue balance using their own subjective "feeling" rather than a scientific perspective [25][26][27][28]. The ligament balancing "feeling" is affected by many factors such as patient obesity, gender, generalized laxity, degree of joint contracture, surgical experience, and even the surgeon's daily condition [29,30].…”
Section: Sensors In Tka 41 General Conceptsmentioning
confidence: 99%
“…However, adequate soft tissue balancing still remains a challenge for many surgeons, especially younger surgeons who lack surgical experience. Further, experienced surgeons traditionally obtain soft tissue balance using their own subjective “feeling” rather than a scientific perspective [ 6 9 ]. The soft tissue balancing “feeling” is affected by factors such as surgical experience, patient’s BMI, gender, generalized laxity, degree of joint contracture and even the surgeon’s daily condition [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hanratty et al hypothesised that capsular stripping could improve flexion and range of motion; however, despite finding an immediate increase in knee flexion, no difference was maintained after 3 months or 1 year [ 12 ]. Reports of treating flexion contracture post-TKA by posterior capsular release or removal of posterior femoral osteophytes have not considered the possible effect on knee AP stability [ 14 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate whether flexion contracture in TKA should be fixed surgically or alternatively treated with continuous physiotherapy postoperatively [ 14 , 22 ]. This study has found that one such surgical treatment, releasing the posterior capsule from its femoral attachment, did not cause a large detrimental increase in AP laxity at time of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation